Chapter Interlude On shortcomings of the instrumentalist view - Schmidt, Jan Cornelius (Taylor & Francis, 2021)
This interlude chapter-between the analysis and assessment of the status-quo (chapters 2-5; first part of the book) and the visions and prospects for the future of interdisciplinary knowledge production (the following chapters 6-8; second part of the book)-addresses shortcomings of the instrumentalist view of interdisciplinarity and its isolated focus on recipes and organization procedures. This chapter questions the positivist fact/value dichotomy; it refers to critical materialist and transcendental pragmatist thinking; it considers viewpoints of environmentalism and reflects on insights from phenomenology and from Martin Heidegger; and it discusses recent developments resulting from a participatory approach among the sciences which could contribute to a new view of human-nature relations (self-organization theory, complex systems theory). Essentially, the interlude chapter paves the way for a critical-reflexive concept of problem-oriented interdisciplinarity. Based on the analysis here, the final three chapters provide a theoretical framework (chapter 6) and present case studies (chapter 7 & 8) showing that a more critical-reflexive perspective in (and with) interdisciplinarity is feasible and can be incorporated in the practice of interdisciplinarity for a sustainable future of our knowledge society.